Effects of supplemental feeds containing different protein energy ratios on the growth and survival of Tilapia Nilotica in brackishwater ponds - Fineman-Kalio, Arthur S.
Nine (9) supplementary diets containing different protein: energy ratios were formulated and fed to Tilapia nilotica fingerlings (average weight 2.90g) in thirty 100 sq. m. fertilize brackishwater pond of the UP-College of Fisheries Brackishwater Aquaculture Center, Leganes, Iloilo from November 7, 1982 to March 7, 1983 as follows: Treatment I ( Control-no feeding but fertilization only); II (20:3,000 kcals) ; III (20: 3,500 kcals); IV (20:4,000 kcals) ; V (25:3,000 kcals ; VI (25 : 3,500 kcals ; VII (25 : 4,000 kcals) ; Viii (30 : 3,000 kcals. ) ; IX (30 : 3,500 kcals) ; and X (30 : 4, 000 kcals). The highest mean weight gain of 102.21g and net production of 25.34 kg/100 sq. m. or equivalent to 2,534.63 kg/ha were obtained from treatment X. A strong interaction between levels of protein and energy in the diets significantly affected weight gain, although there were no significant differences in net production of fish in different treatments probably due to influence of additional harvest of fingerlings from reproduction. Within the 30% protein level, increasing energy levels from 3,000 kcals to 4,000 kcals had synergistic effects on the growth of fish. However, high energy levels of 3,500 kcals to 4,000 kcals in combination with either 20% or 25% protein apparently interfered with protein utilization resulting in lower mean weights. Lower mean weight of fish was also obtained in the high protein-low energy diet (30 : 3,000 kcals.) which suggests that non-protein energy required for protein catabolism was inadequate. The best feed conversion was obtained in treatment IX (1.55) while the poorest was in treatment VI (2.04). Fat and not protein deposition was affected by the protein-energy ratios in the supplemental feeds. Condition factor was best in treatment X with an index of 5.75 and lowest in treatment IV (5.32) and treatment VII (5.46) due to higher fat content of harvested fish. Low condition index in control (treatment I) at 1.5011 was a direct result of low fat deposition in the body. Temperatures below 20℃ slowed down growth rate of fish in all treatments. Meanwhile, reproduction occurred in all treatments at lower salinities of 17-29 ppt. Contribution to net production of fish at harvest by fingerlings from the reproduction ranged from a low mean weight of 355.09 kg/ha in treatment VI to a high 1,059.61 kg/ha in treatment X among the fed treatments. However, simple cost and returns analysis revealed that treatment II (20 : 3,000 kcals.) gave the highest net income of ₱15.09 and ₱13.94 per kilo of fish marketed, based on Iloilo and Metro Manila market prices, respectively mainly due to lower cost of the feed.